2009
DOI: 10.1002/cne.22049
|View full text |Cite
|
Sign up to set email alerts
|

Sensory innervation of the calvarial bones of the mouse

Abstract: Migraine sufferers frequently testify that their headache feels as if the calvarial bones are deformed, crushed, or broken (Jakubowski et al., 2006). This has lead us to postulate that nociceptive fibers supply the calvarial bones. We studied sensory innervation of the calvaria in coronal and horizontal sections of whole-head preparations of postnatal and adult mice, using immunostaining of peripherin – a marker of thinly-myelinated and unmyelinated fibers – and calcitonin gene-related peptide (CGRP) – a marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(185 citation statements)
references
References 43 publications
12
168
0
5
Order By: Relevance
“…3G). By contrast, fibers that are positive for peripherin, a marker for prospective unmyelinated axons (Kosaras et al, 2009;Lariviere et al, 2002), were unaffected in Ret GFP/GFP mice (Fig. 3I), consistent with the idea that Ret + neurons are myelinated mechanoreceptive neurons, although the staining specificity of NF-200 and peripherin is somewhat controversial (Jackman and Fitzgerald, 2000).…”
Section: Retsupporting
confidence: 80%
“…3G). By contrast, fibers that are positive for peripherin, a marker for prospective unmyelinated axons (Kosaras et al, 2009;Lariviere et al, 2002), were unaffected in Ret GFP/GFP mice (Fig. 3I), consistent with the idea that Ret + neurons are myelinated mechanoreceptive neurons, although the staining specificity of NF-200 and peripherin is somewhat controversial (Jackman and Fitzgerald, 2000).…”
Section: Retsupporting
confidence: 80%
“…Because the PVS is considered essential for clearance of brain solutes (Abbott, 2004;Carare et al, 2008;Iliff et al, 2012Iliff et al, , 2014Jessen et al, 2015), we sought to determine the effects of CSD on interstitial/glymphatic flow. Accordingly, we injected dye (3 kDa FITC-dextran) into the frontal cortex (3.5 mm anterior to the imaging window) of ubiquitously labeled tdTomato red fluorescent mice, and observed how quickly the dye filled the posterior PVS in CSD-induced and non-CSDinduced mice (Fig.…”
Section: Csd Impairs Glymphatic Flowmentioning
confidence: 99%
“…This closure is not likely to be simply a result of the CSD-induced changes in vessel diameter, because it was maximal throughout both the initial dilation and constriction exhibited by the arteries, and because the closure of the paravenous space (i.e., PVS near pial veins) occurred in the absence of any detectable change in the diameter of the pial vein. Based on reports of neuronal (Takano et al, 2007) and astrocytic endfeet (Tomita et al, 2011) swelling after CSD, it may be more likely that the closure of the PVS is secondary to such swelling-especially considering that astrocytic endfeet form the outer wall of the PVS (Jessen et al, 2015). Also, we observed that the PVS around penetrating arteries may close seconds before it closes around the surface arteries, which raises the possibility that the CSD-induced parenchymal swelling spreads from deep layer I up to the pia.…”
Section: Mechanism Of Pvs Closurementioning
confidence: 99%
See 2 more Smart Citations